Anti-inflammatory effects of embelin in A549 cells and human asthmatic airway epithelial tissues. (2nd January 2018) - Lee, In-Seung; Cho, Dong-Hyuk; Kim, Ki-Suk; Kim, Kang-Hoon; Park, Jiyoung; Kim, Yumi; Jung, Ji Hoon; Kim, Kwanil; Jung, Hee-Jae; Jang, Hyeung-Jin
Abstract: Objective: Allergic asthma is the most common type in asthma, which is defined as a chronic inflammatory disease of the lung. In this study, we investigated whether embelin (Emb), the major component of Ardisia japonica BL. (AJB), exhibits anti-inflammatory effects on allergic asthma via inhibition of NF-κB activity using A549 cells and asthmatic airway epithelial tissues. Methods: Inflammation was induced in A549 cells, a human airway epithelial cell line, by IL-1β (10 ng/ml) treatment for 4 h. The effects of Emb on NF-κB activity and COX-2 protein expression in inflamed airway epithelial cells and human asthmatic airway epithelial tissues were analyzed via western blot. The secretion levels of NF-κB-mediated cytokines/chemokines, including IL-4, 6, 9, 13, TNF-α and eotaxin, were measured by a multiplex assay. Results: Emb significantly blocked NF-κB activity in IL-1β-treated A549 cells and human asthmatic airway epithelial tissues. COX-2 expression was also reduced in both IL-1β-treated A549 cells and asthmatic tissues Emb application. Emb significantly reduced the secretion of IL-4, IL-6 and eotaxin in human asthmatic airway epithelial tissues by inhibiting activity of NF-κB. Conclusions: The results of this study suggest that Emb may be used as an anti-inflammatory agent via inhibition of NF-κB and related cytokines.